Investigation on coaxial visual characteristics of molten pool in laser-based directed energy deposition of AISI 316L steel - Tang, Zi-jue; Liu, Wei-wei; Zhu, Li-na; Liu, Zhi-chao; Yan, Zhao-rui; Lin, Dong; Zhang, Zhao; Zhang, Hong-Chao (Journal of materials processing technology, 2021)
•Molten pool can be divided into three regions to describe LDED process.•Coaxial visual characteristics can reflect metallurgical behaviors of molten pool.•There is a definite relationship between visual and temperature characteristics.•Visual characteristics can be used to monitor process state and product qualities. Laser-based directed energy deposition (LDED), an additive manufacturing technique, has received increasing attention from the industry and academia. Unstable reliability and poor repeatability in the production of metal parts are two challenges currently faced by LDED. In-situ monitoring and adaptive control technology based on visual characteristics serves as effective methods to ensure part quality and process stability. Although molten pools directly influence metallurgical behaviors in LDED, their visual characteristics still require further investigation. In this work, a coaxial visual image of a molten pool was captured during the LDED of 316 L material and divided into three regions. Then, the evolutionary behaviors of different regions during single-layer single-track processing, multi-layer one-track stacking, and one-layer multi-track overlapping were analyzed. Additionally, the metallurgical behaviors of the molten pool, including the formation mechanisms of slag characteristics, were explicated. Results showed that molten pool characteristics could be presented and described with visual images reasonably. These characteristics could indicate the state of melting, heat conduction and convection, and overlapping position. Meanwhile, coaxial visual characteristics were closely related to product qualities. This work could enhance the understanding of LDED process mechanisms and improve real-time monitoring capability. The proposed approach for the determination of molten pool characteristics is expected to be applicable to other materials.